Advancing Flood predication based on integrating Traditional and Deep Learning Techniques - Mahdi, Muthana S.; Abbas, Ishraq Khudhair; Muhammed, Ban M.; Abbas, Hiba Abdulrazzaq (Journal La Multiapp, 2024)
Flood prediction is critical for reducing the negative effects of catastrophes. This study investigates the use of classical and deep learning algorithms to accurately anticipate flood levels using past ecological information. The study takes two approaches: linear regression and deep neural networks (DNN). These models are trained and evaluated using historical records stretching years, as well as moisture, temperature, and rainfall measurements. Visualization tools, such as development/validation reduction charts projected against real floodwater level graphs, can help understand model learning behaviors and efficacy. Furthermore, a combination model method is investigated, which combines forecasts from both approaches and has the promise to improve the accuracy of predictions. Future forecasts for the year 2025 can be generated using expected atmospheric conditions, illustrating the models' usefulness in projecting eventual floodwater levels. Measures of assessment and visualization results demonstrate the effectiveness of deep learning technologies in improving flooding predictions when contrasted with classic conventional techniques. This investigation advances flooding forecasting skills by combining known statistical approaches and new deep learning algorithms, thereby helping in active catastrophe control and vulnerability planning.